Opportunities and advancement in interior design careers a career guide based on the preferences of interior design students of the university of the Philippines - Reyes, Cristina Tayag
The interior design industry has come a long way in its level of professionalism. In the Philippines and in abroad there lies a vast range of career opportunities and advancement in the interior design field. The main objective of the study is to offer a career guide for interior design student of the University of the Philippines (U.P.). It sought to find out what things are needed to be considered for professional advancement in the field. To achieve this, the researcher had to first determine what the students' preferences are and the factors affecting these choices by means of a survey. The respondents of a survey were interior design students of U.P enrolled during the second semester of academic year 1992 to 1993. Stratified purposive sampling was used by the researcher in selecting the representative sample. The nominal level of measurement was used in the study with the main variables being the interior design students, their career preference and the reasons for these preferences. The analysis of the data was descriptive and was done by categorization. The study also aimed to present a list of career opportunities, local and abroad, that are available to the interior design graduate. Library and documentary research was done by categorization. The study also aimed to present a list of career opportunities, local and abroad, that are available to the interior design graduate. Library and documentary research was done to produce the list. The source of the local aspect of the study was a local practitioner of the interior design. The relationships between the independent and dependent variables of the study, observed in the representative sample, were conclusive. This made the observations extensible to the whole population of interior design students of the University of the Philippines. The highlights of the results of the study were presented as part of the summary and conclusions together with a direct answer to the research problem. Implications with regards to the importance of the results and recommendations for further research was also given at the end of the study.